A cobertura do caso Calabresi na mídia impressa e o conflito entre o infante exposto e o sujeito de direitos - SOUZA, Lillian Bento de (2009)
A torture case that had as victim a 12 year-old girl is denounced by some neighbors of the aggressor, the entrepreneur of high middle class who lived in a noble quarter of Goiânia (GO), Silvia Calabresi, became subject of analysis in the Brazilian media, in special, the provincial press since March 17th of 2008, when the case was denounced to the Police. This work searches to identify the Discursive Formation that leads the speech of the media about the relation of the violence with childhood from the Analysis of Speech (AD) proposed by Michel Pêcheux, Michel Foucault and, finally, from the analysis of the Archaeological Method, argued by Freda Indursky (2007). The path of the representation of childhood, since the displayed child, represented by indigenous children of the Brazil Colony, passing by the notion of minor and marginalized child, legally consolidated with the Codes of Minor, until the citizenship in development age starred from the Statute of the Child and the Adolescent (Law 8,069/90), appears as the first conducting wire to identify the Discursive Formation that leads the media s speech in this specific police covering case. The notion of violence and the acceptance of the torture misinterpreted during many decades as educational process present on the parentschildren relation also come up at the aggressor s speech, who justifies the torture sessions as she was educating the child-victim. Finally, the notion of citizen of rights seems more consolidated when the torture is faced as something unacceptable in the vein of the contemporary society, considering strange the fact that the violent act had occurred in the heart of the middle class. There is some strangeness in this fact witch comes from the consolidated notion in the common sense that violence is a characteristic of poorer classes. Ally to this trajectory of the notion of childhood, violence and torture is the process of the news production, witch, with its own characteristics, redirects the journalistic text, without however, turn aside itself from the Discursive Formation where it is inserted.